Internalisasi Nilai Moderasi Beragama Terhadap Pendidikan Karakter Berbasis Pendidikan Kepramukaan di Unit Kegiatan Mahasiswa Pramuka Universitas Bengkulu - Ahmad Singgih; Ali Akbarjono (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2025)
Religious moderation is a concept emphasizing mutual respect and tolerance among different religious groups. Therefore, this thesis aims to explore the internalization of religious moderation values in character education based on scouting education at the Scout Student Activity Unit of Bengkulu University. This study employs a descriptive qualitative research methodology. Primary respondents include the head of the scout unit, the head of the male scout council, the head of the female scout council, the sub-coordinator of student welfare, and members of the scout unit at Bengkulu University. Secondary respondents consist of books, journals, and other scholarly studies. Data collection techniques include observation, interviews, and documentation. Data validity is ensured through triangulation. Data analysis is conducted through data reduction, data presentation, and drawing conclusions. The findings indicate that the internalization of religious moderation values in character education based on scouting education at the Scout Student Activity Unit of Bengkulu University is achieved through various internalization efforts: first, the process of internalization is carried out through activities outlined in the work program, such as the implementation of religious moderation camps and mentoring, diversity camps, and Weekend Sharing Sessions; second, the application of values in daily activities; third, reinforcement and development. Supporting factors for internalizing religious moderation values in scouting-based character education at Bengkulu University include: a) inclusive leadership, b) structured work programs, c) supportive organizational culture, d) campus environment support, e) media utilization, and f) active member involvement. However, the process faces challenges such as: a) lack of understanding of religious moderation, b) exclusive culture, c) limited resources, d) ineffective communication, and e) negative external influences. Addressing these challenges and maximizing supporting factors are key to the successful internalization of religious  moderation values.